Supramolecular chiral spiral nano-catalyst as well as preparation method and application thereof
The construction of supramolecular chiral helical nanocatalysts through solvent-induced assembly solves the limitations of chiral catalysts in the prior art in terms of enantioselectivity, and achieves efficient selective catalysis of dopa molecules.
Patent Information
- Application Number
- CN202411750992.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-15
AI Technical Summary
Existing chiral catalysts have stability, selectivity and activity limitations in achieving high enantioselectivity, which is difficult to meet the needs of large-scale industrial production.
High optical purity left-hand/right-hand helical nanomaterials were constructed by solvent-induced assembly strategies, and Fe3O4 nanoparticles were loaded on the surfaces of these materials to form supramolecular chiral helical nanocatalysts.
Enantioselective catalysis of R/S-DOPA was achieved, the catalytic efficiency was significantly improved, and the selectivity factor reached 1.98/1.83, meeting the needs of industrial production.
Smart Images

Figure CN119819365A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of supramolecular chiral self-assembly and asymmetric catalysis, and in particular to a supramolecular chiral helical nanocatalyst and a preparation method and application thereof. Background Art
[0002] In recent years, chiral compounds have been increasingly used in medicine, pesticides, fragrances and other fields, and their market share has increased year by year. Asymmetric catalysis is an important way to synthesize compounds with specific chirality. Therefore, the development of chiral nanocatalysts with high enantioselectivity has become an important hotspot in the current scientific research field.
[0003] The general idea of constructing chiral catalysts in the prior art is to combine the chiral environment with the catalytic center to achieve enantioselective catalysis of the reactants, where the chiral environment generally works through molecular chirality. However, this method is often limited by the stability, selectivity and activity of the catalyst in practical applications, and cannot achieve high enantioselectivity, making it difficult to meet the needs of large-scale industrial production.
[0004] In recent years, scientists have discovered that biomacromolecules such as proteins and DNA in organisms not only have molecular chirality, but also exhibit supramolecular chirality through their unique helical morphology. This supramolecular chiral helical morphology can not only enhance the chiral characteristics of related materials, but also further improve the asymmetric catalytic performance of catalysts by regulating the enantioselectivity of the catalytic center. This discovery provides a new idea for the construction of high-performance chiral catalysts. However, the construction of supramolecular chiral helical nanomaterials with high optical purity based on achiral compounds is still difficult.
[0005] Based on the above findings, further construction of supramolecular chiral helical nanocatalysts provides an effective way to improve the asymmetric catalytic selectivity of chiral compounds. The present invention proposes a solvent-induced assembly strategy for constructing left-handed / right-handed helical nanomaterials with high optical purity. This strategy induces the nanomaterials to form a stable helical structure by precisely controlling the composition and conditions of the solvent. At the same time, the present invention also loads Fe3O4 nanoparticles on the surface of these helical nanomaterials as catalytic active centers. By optimizing the loading amount and distribution of Fe3O4 nanoparticles, the enantioselective catalysis of R / S-DOPA (two enantiomers of DOPA) is successfully achieved. This achievement not only provides a new method for the efficient synthesis of DOPA, but also provides a reference idea for the synthesis of other chiral compounds. Summary of the invention
[0006] Technical problems to be solved: In view of the technical problems in the prior art that chiral catalysts cannot efficiently achieve asymmetric catalytic selectivity of chiral compounds, the present invention proposes a supramolecular chiral helical nanocatalyst and a preparation method and application thereof. The supramolecular chiral helical nanocatalyst is based on the composite of supramolecular left-handed / right-handed helical nanomaterials and Fe3O4 nanoparticles, and two supramolecular chiral nanocatalysts with excellent chiral selectivity are constructed, which can be used to selectively catalyze DOPA molecules of specific configurations.
[0007] Technical solution: The first object of the present invention is to provide a method for preparing a supramolecular chiral helical nanocatalyst, the steps of which are as follows:
[0008] Step 1, dissolving 5-aminoisophthalic acid (AIPA) and n-phenyl-p-phenylenediamine in ultrapure water, then adding ultrapure water containing R / S camphorsulfonic acid (CSA), ultrasonicating the mixture until the solution is clear, adding ammonium persulfate (APS), and placing the mixture in a water bath to react to obtain R / S-PAIPA nanofibers (R / S-PAIPA (Fiber));
[0009] Step 2, transferring the R / S-PAIPA nanofibers obtained in step 1 into ethanol for assembly. After the assembly is completed, the R / S-PAIPA nanofibers are assembled into R / S-PAIPA helical nanoribbons (R / S-PAIPA (Helix) helical nanoribbons);
[0010] Step 3: Mix the R / S-PAIPA helical nanoribbons with Fe3O4 nanoparticles respectively to obtain two supramolecular chiral nanocatalysts (R / S-PAIPA (Helix) -Fe3O4) with excellent chiral selectivity.
[0011] Preferably, in step 1, the molar ratio of R / S camphorsulfonic acid, 5-aminoisophthalic acid, ammonium persulfate and n-phenyl-p-phenylenediamine is 23-28:1:3:0.025.
[0012] Preferably, in step 1, the mixture is placed in a 40° C. water bath for reaction.
[0013] Preferably, in step 2, the ratio of R / S-PAIPA nanofibers to ethanol is 5-8 mg: 3-5 mL.
[0014] Preferably, in the step 2, the R / S-PAIPA nanofibers obtained in the step 1 are transferred to ethanol for assembly, and the assembly is completed by standing at 25° C. for no less than 5 days.
[0015] Preferably, in step three, the R / S-PAIPA spiral nanobelts are mixed with Fe3O4 respectively as follows: water is used as a solvent, Fe3O4 is dissolved in water, and then an aqueous solution containing R / S-PAIPA spiral nanobelts is added, the mass ratio of Fe3O4 and R / S-PAIPA spiral nanobelts is 0.5-2mg:15mg, and the mixture is mixed at room temperature for 4h. After washing three times with ultrapure water and ethanol, the unloaded Fe3O4 is removed to obtain two supramolecular chiral nanocatalysts (R / S-PAIPA (Helix) -Fe3O4) with excellent chiral selectivity.
[0016] The second object of the present invention is to provide a supramolecular chiral helical nanocatalyst prepared based on the above method.
[0017] The third object of the present invention is to provide an application of the supramolecular chiral helical nanocatalyst in the enantioselective catalysis of R / S-DOPA.
[0018] Beneficial effects: (1) The solvent-induced assembly method provided by the present invention can be used to construct supramolecular chiral nanomaterials with obvious spiral morphology; compared with the prior art "A supramolecular chiral nanocatalyst and its preparation method and application (ZL2022100149078)", the supramolecular chiral arrangement of the nanomaterials constructed by this technology is qualitatively improved.
[0019] (2) The supramolecular chiral R / S-PAIPA(Helix)-Fe3O4 provided by the present invention can selectively catalyze DOPA molecules of a specific configuration. R-PAIPA(Helix)Fe3O4 has a higher catalytic efficiency for R-DOPA, while S-PAIPA(Helix)Fe3O4 has a higher catalytic efficiency for S-DOPA. Compared with the prior art "A supramolecular chiral nanocatalyst and its preparation method and application (ZL 2022100149078)", the chiral helical catalyst R / S-PAIPA(Helix)-Fe3O4 constructed by this technology has significantly improved the selective catalytic efficiency of DOPA substrates, and the selectivity factor is as high as 1.98 / 1.83. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 TEM images of R / S-PAIPA (Fiber) nanofibers, wherein (a) and (b) are TEM images of R-PAIPA (Fiber) nanofibers, and (c) and (d) are TEM images of S-PAIPA (Fiber) nanofibers;
[0021] Figure 2TEM images and SEM images of R / S-PAIPA (Helix) helical nanoribbons, wherein (a) and (d) are TEM images of R-PAIPA (Helix) helical nanoribbons, (e) and (h) are TEM images of S-PAIPA (Helix) helical nanoribbons, (b) and (c) are SEM images of R-PAIPA (Helix) helical nanoribbons, and (f) and (g) are SEM images of S-PAIPA (Helix) helical nanoribbons;
[0022] Figure 3 SEM images and TEM images of R / S-PAIPA(Fiber)-Fe3O4 and R / S-PAIPA(Helix)-Fe3O4, wherein (a) and (a1) are SEM images and TEM images of R-PAIPA(Fiber)-Fe3O4, (c) and (c1) are SEM images and TEM images of S-PAIPA(Fiber)-Fe3O4, (b) and (b1) are SEM images and TEM images of R-PAIPA(Helix)-Fe3O4, (d) and (d1) are SEM images and TEM images of S-PAIPA(Helix)-Fe3O4;
[0023] Figure 4 The UV-Vis and CD spectra of R / S-PAIPA(Fiber)-Fe3O4 and R / S-PAIPA(Helix)-Fe3O4, wherein (a) is the UV-Vis spectrum of R / S-PAIPA(Fiber)-Fe3O4, (b) is the CD spectrum of R / S-PAIPA(Fiber)-Fe3O4, (c) is the UV-Vis spectrum of R / S-PAIPA(Helix)-Fe3O4, and (d) is the CD spectrum of R / S-PAIPA(Helix)-Fe3O4;
[0024] Figure 5 The time-dependent absorbance change curves of 2.5mM DOPA enantiomers at 475nm with R / S-PAIPA(Fiber)-Fe3O4 and R / S-PAIPA(Helix)-Fe3O4 as catalysts. In the figure, (a) is the catalysis of R / S-DOPA with R-PAIPA(Fiber)-Fe3O4 as the catalyst; (b) is the catalysis of R / S-DOPA with S-PAIPA(Fiber)-Fe3O4 as the catalyst; (c) is the catalysis of R / S-DOPA with R-PAIPA(Helix)-Fe3O4 as the catalyst; (d) is the catalysis of R / S-DOPA with S-PAIPA(Helix)-Fe3O4 as the catalyst. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0026] The sources of raw materials in the examples of the present invention are as follows:
[0027] 5-Aminoisophthalic acid was purchased from Shanghai Aladdin Biochemical Co., Ltd. (Shanghai, China);
[0028] n-Phenyl-p-phenylenediamine was purchased from Sigma-Aldrich;
[0029] Camphorsulfonic acid (R-CSA) and camphorsulfonic acid (S-CSA) were purchased from Shanghai Aladdin Biochemical Co., Ltd. (Shanghai, China);
[0030] Ammonium persulfate was purchased from Sinopharm Chemical Reagent Co., Ltd. (Shanghai);
[0031] FeCl3.6H2O and sodium oleate required for the synthesis of Fe3O4 nanoparticles were purchased from China Pharmaceutical Chemical Reagent Co., Ltd. (Shanghai). The synthesis method of Fe3O4 nanoparticles in the examples of this specification is as follows:
[0032] 10.8g of ferric chloride (FeCl3.6H2O) and 36.5g of sodium oleate were dissolved in a solvent mixture containing 60mL of distilled water, 80mL of ethanol and 140mL of hexane. The mixture was heated at a temperature of 60°C for 4 hours. Throughout the process, the mixture was stirred continuously until the sodium oleate was completely dissolved. After the reaction was completed, the upper organic layer was washed three times with 90mL of distilled water. The final product after removing hexane with a rotary evaporator was a viscous reddish-brown oily substance, i.e., iron oleate. Then, 1.8g of iron oleate and 0.285g of oleic acid were dissolved in 10g of 1-octadecene, respectively, and dissolved in a N2 atmosphere at room temperature. After 20 minutes, the reaction solution was heated to 320°C (18°C / min) and maintained for 60min. Subsequently, the above reaction solution was cooled to room temperature, washed three times with a mixture of hexane and acetone, and the resulting hydrophobic Fe3O4 nanoparticles were dispersed in 36mL of tetrahydrofuran. Next, in order to modify the hydrophobic Fe3O4 nanoparticles to hydrophilic, 50 mg of 3,4-dihydroxybenzoic acid was dissolved in 6 mL of THF and heated to 50°C. Subsequently, a THF dispersion of hydrophobic Fe3O4 nanoparticles (6 mL) was gradually added. The reaction mixture was stirred at 50°C for three hours and then cooled to room temperature. Then, 500 μL of 0.5 M NaOH was added to the mixture to precipitate Fe3O4 nanoparticles. After centrifugation at 4000 rpm, the precipitate was redispersed in water (pH = 4).
[0033] DOPA (R / S) was purchased from Shanghai Aladdin Biochemical Co., Ltd. (Shanghai, China).
[0034] Comparative Example 1 Preparation method of supramolecular chiral R-PAIPA (fiber)-Fe3O4:
[0035] Step 1. Dissolve AIPA (72 mg) and n-phenyl-p-phenylenediamine (2 mg) in 3 mL of ultrapure water, then add 5 mL of ultrapure water containing camphorsulfonic acid (R-CSA, 2.323 g), and sonicate the mixture until the solution is clear. After 30 minutes, add 2 mL of ammonium persulfate (APS, 274 mg) aqueous solution to the above solution. Place the above mixture in a 40°C water bath to react for 24 hours, then centrifuge the sample and wash 3 times with ultrapure water to obtain R-PAIPA (Fiber). The molar ratio of camphorsulfonic acid: 5-aminodibenzoic acid: ammonium persulfate: n-phenyl-p-phenylenediamine is 25:1:3:0.025. By Figure 1 (a) and (b) show that R-PAIPA (Fiber) is a nanofiber with a diameter of about 20 nm and no obvious helical structure.
[0036] Step 2: Stir 0.5 mg Fe3O4 (4 mL) aqueous solution at 60°C for 30 min, then add 8 mL of aqueous solution containing 15 mg R-PAIPA (Fiber), mix at room temperature for 4 hours, wash three times with ultrapure water and ethanol to remove unloaded Fe3O4, and obtain R-PAIPA (Fiber)-Fe3O4.
[0037] Depend on Figure 3 (a) SEM image and Figure 3 From the TEM image (a1), we can see that Fe3O4 nanoparticles are successfully modified on the surface of R-PAIPA (Fiber). Figure 4 From the UV-Vis spectrum of (a), it can be seen that R-PAIPA(Fiber)-Fe3O4 has obvious absorption peaks at 220nm and 430nm. Figure 4 From the CD spectrum of (b), we can see that R-PAIPA(Fiber)-Fe3O4 exhibits a weak positive Cotton effect at 450nm and a weak negative Cotton effect at 240nm.
[0038] Comparative Example 2 Preparation method of supramolecular chiral S-PAIPA (fiber)-Fe3O4:
[0039] Step 1. Dissolve AIPA (72 mg) and n-phenyl-p-phenylenediamine (2 mg) in 3 mL of ultrapure water, then add 5 mL of ultrapure water containing camphorsulfonic acid (S-CSA, 2.323 g), and sonicate the mixture until the solution is clear. After 30 minutes, add 2 mL of ammonium persulfate (APS, 274 mg) aqueous solution to the above solution. Place the above mixture in a 40°C water bath to react for 24 hours, then centrifuge the sample and wash 3 times with ultrapure water to obtain S-PAIPA (Fiber). The molar ratio of camphorsulfonic acid: 5-aminodibenzoic acid: ammonium persulfate: n-phenyl-p-phenylenediamine is 25:1:3:0.025. By Figure 1 (c) and (d) show that S-PAIPA (Fiber) is a nanofiber with a diameter of about 20 nm and no obvious helical structure.
[0040] Step 2: Stir 0.5 mg Fe3O4 (4 mL) aqueous solution at 60°C for 30 min, then add 8 mL of aqueous solution containing 15 mg S-PAIPA (Fiber), mix at room temperature for 4 hours, wash three times with ultrapure water and ethanol to remove unloaded Fe3O4, and obtain S-PAIPA (Fiber)-Fe3O4.
[0041] Depend on Figure 3 (c) SEM image and Figure 3 From the TEM image (c1), we can see that Fe3O4 nanoparticles are successfully modified on the surface of S-PAIPA (Fiber). Figure 4 From the UV-Vis spectrum of (a), it can be seen that S-PAIPA(Fiber)-Fe3O4 has obvious absorption peaks at 220nm and 430nm, which is basically consistent with the absorption spectrum of R-PAIPA(Fiber)-Fe3O4. Figure 4 From the CD spectrum of (b), we can see that S-PAIPA(Fiber)-Fe3O4 exhibits a weak negative Cotton effect at 450nm and a weak positive Cotton effect at 240nm, which is a mirror image of the CD spectrum of R-PAIPA(Fiber)-Fe3O4.
[0042] Example 1 Preparation method of R-PAIPA (Helix) -Fe3O4:
[0043] Step 1: Dissolve AIPA (72 mg) and n-phenyl-p-phenylenediamine (2 mg) in 3 mL of ultrapure water, then add 5 mL of ultrapure water containing camphorsulfonic acid (R-CSA, 2.323 g), and ultrasonicate the mixture until the solution is clear. After 30 min, add 2 mL of ammonium persulfate (APS, 274 mg) aqueous solution to the above solution. The above mixture is placed in a 40 ° C water bath for reaction for 24 h, and then the sample is centrifuged and washed 3 times with ultrapure water to obtain R-PAIPA (Fiber). The molar ratio of camphorsulfonic acid: 5-aminodiphenyl acid: ammonium persulfate: n-phenyl-p-phenylenediamine is 25:1:3:0.025.
[0044] Step 2: Disperse 8 mg of freshly prepared R-PAIPA (Fiber) in 4 mL of ethanol. Shake the mixture for 2 minutes and then let it stand at 25° C. for 5 days to obtain R-PAIPA (Helix) helical nanoribbons. Figure 2 The TEM images of (a) and (d) and the SEM images of (b) and (c) show that the R-PAIPA (Helix) helical nanoribbons exhibit obvious right-handed helices.
[0045] Step 3: Stir 0.5 mg Fe3O4 (4 mL) aqueous solution at 60°C for 30 min, then add 8 mL of aqueous solution containing 15 mg R-PAIPA (Helix), mix at room temperature for 4 hours, wash three times with ultrapure water and ethanol to remove unloaded Fe3O4, and obtain R-PAIPA (Helix) -Fe3O4.
[0046] Depend on Figure 3 (b) SEM image and Figure 3 From the TEM image (b1), it can be seen that Fe3O4 nanoparticles are successfully modified on the surface of R-PAIPA(Helix). Figure 4 From the UV-Vis spectrum of (c), it can be seen that R-PAIPA(Helix)-Fe3O4 has obvious absorption peaks at 220nm and 460nm. Figure 4 The CD spectrum in (d) shows that R-PAIPA(Helix)-Fe3O4 exhibits a strong positive Cotton effect at 450nm and a strong negative Cotton effect at 240nm. Due to the formation of the helical morphology, the CD signal of R-PAIPA(Helix)-Fe3O4 is significantly improved compared with R-PAIPA(Fiber)-Fe3O4.
[0047] Example 2 Preparation method of S-PAIPA (Helix) -Fe3O4:
[0048] Step 1: Dissolve AIPA (72 mg) and n-phenyl-p-phenylenediamine (2 mg) in 3 mL of ultrapure water, then add 5 mL of ultrapure water containing camphorsulfonic acid (S-CSA, 2.323 g), and ultrasonicate the mixture until the solution is clear. After 30 min, add 2 mL of ammonium persulfate (APS, 274 mg) aqueous solution to the above solution. The above mixture is placed in a 40 ° C water bath for reaction for 24 h, and then the sample is centrifuged and washed 3 times with ultrapure water to obtain S-PAIPA (Fiber). The molar ratio of camphorsulfonic acid: 5-aminodiphenyl acid: ammonium persulfate: n-phenyl-p-phenylenediamine is 25:1:3:0.025.
[0049] Step 2: Disperse 8 mg of freshly prepared S-PAIPA (Fiber) in 4 mL of ethanol. Shake the mixture for 2 minutes and then let it stand at 25° C. for 5 days to obtain S-PAIPA (Helix) helical nanoribbons. Figure 2 The TEM images of (e) and (h) and the SEM images of (f) and (g) show that the S-PAIPA (Helix) helical nanoribbons exhibit obvious left-handed helices.
[0050] Step 3: Stir 0.5 mg Fe3O4 (4 mL) aqueous solution at 60°C for 30 min, then add 8 mL of aqueous solution containing 15 mg S-PAIPA (Helix), mix at room temperature for 4 hours, wash three times with ultrapure water and ethanol to remove unloaded Fe3O4, and obtain S-PAIPA (Helix) -Fe3O4.
[0051] Depend on Figure 3 (d) SEM images and Figure 3 From the TEM image (d1), it can be seen that Fe3O4 nanoparticles are successfully modified on the surface of S-PAIPA (Helix). Figure 4 From the UV-Vis spectrum of (c), it can be seen that S-PAIPA(Helix)-Fe3O4 has obvious absorption peaks at 220nm and 460nm. Figure 4 The CD spectrum in (d) shows that S-PAIPA(Helix)-Fe3O4 exhibits a strong negative Cotton effect at 450nm and a strong positive Cotton effect at 240nm. Due to the formation of the helical morphology, the CD signal of S-PAIPA(Helix)-Fe3O4 is significantly improved compared with S-PAIPA(Fiber)-Fe3O4.
[0052] Example 3
[0053] Same as Example 1, except that the molar ratio of R-type camphorsulfonic acid, 5-aminoisophthalic acid, ammonium persulfate, and n-phenyl-p-phenylenediamine in step 1 is 23:1:3:0.025. The ratio of R-PAIPA nanofibers to ethanol in step 2 is 5 mg:3 mL. The mass ratio of Fe3O4 to R-PAIPA helical nanoribbons in step 3 is 0.5 mg:15 mg.
[0054] Example 4
[0055] In the step 1, the molar ratio of S-camphorsulfonic acid, 5-aminoisophthalic acid, ammonium persulfate, and n-phenyl-p-phenylenediamine is 28:1:3:0.025. In the step 2, the ratio of S-PAIPA nanofibers to ethanol is 8 mg:5 mL. In the step 3, the mass ratio of Fe3O4 to S-PAIPA spiral nanoribbons is 2 mg:15 mg.
[0056] Application Examples
[0057] Asymmetric catalytic study of supramolecular chiral R-PAIPA(Fiber)-Fe3O4, S-PAIPA(Fiber)-Fe3O4, R-PAIPA(Helix)-Fe3O4 and S-PAIPA(Helix)-Fe3O4 catalysts on R / S-DOPA:
[0058] The catalytic oxidation efficiency of R / S-DOPA by different catalysts was evaluated by monitoring the absorbance change of R / S-DOPA at 475nm over time. The reaction volume was 3mL buffer solution (pH 7.0, 37℃), the concentration of R-PAIPA(Fiber)-Fe3O4 or S-PAIPA(Fiber)-Fe3O4 or R-PAIPA(Helix)-Fe3O4 or S-PAIPA(Helix)-Fe3O4 catalyst was 0.1mg / mL, the concentration of DOPA substrate (R / S-DOPA) was 2.5mM, and the concentration of H2O2 was 50mM.
[0059] Depend on Figure 5 (a) It can be seen that the catalytic rate of R-PAIPA(Fiber)-Fe3O4 to S-DOPA is faster than that of R-DOPA. Figure 5 (b) It can be seen that the catalytic rate of S-PAIPA(Fiber)-Fe3O4 to R-DOPA is also faster than that of S-DOPA. Figure 5 (c) It can be seen that under the same conditions, the catalytic rate of the supramolecular chiral R-PAIPA(Helix)-Fe3O4 on S-DOPA is greater than that of R-DOPA. Figure 5(d) It can be seen that under the same conditions, the catalytic rate of supramolecular chiral S-PAIPA(Helix)-Fe3O4 on R-DOPA is greater than that of S-DOPA. Figure 5 The results also show that the selective catalytic difference of R / S-PAIPA(Helix)-Fe3O4 to R / S-DOPA is significantly greater than that of R / S-PAIPA(Fiber)-Fe3O4, indicating that the helical morphology induced by solvent regulation is conducive to the improvement of asymmetric catalytic selectivity.
[0060] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned implementation modes, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned implementation modes can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the implementation modes of the present invention.
Claims
1. A method for preparing a supramolecular chiral helical nanocatalyst, characterized in that: Here are the steps: Step 1, dissolving 5-aminoisophthalic acid and n-phenyl-p-phenylenediamine in ultrapure water, then adding ultrapure water containing R / S camphorsulfonic acid, ultrasonicating the mixture until the solution is clear, adding ammonium persulfate, and placing the mixture in a water bath to react to obtain R / S-PAIPA nanofibers; Step 2, transferring the R / S-PAIPA nanofibers obtained in step 1 into ethanol for assembly. After the assembly is completed, the R / S-PAIPA nanofibers are assembled into R / S-PAIPA spiral nanoribbons; Step 3: Mix the R / S-PAIPA helical nanoribbons with Fe3O4 nanoparticles respectively to obtain two supramolecular chiral nanocatalysts with excellent chiral selectivity.
2. The method for preparing a supramolecular chiral helical nanocatalyst according to claim 1, characterized in that: In the step 1, the molar ratio of R / S type camphorsulfonic acid, 5-aminoisophthalic acid, ammonium persulfate and n-phenyl-p-phenylenediamine is 23-28:1:3:0.
025.
3. The method for preparing a supramolecular chiral helical nanocatalyst according to claim 1, characterized in that: In the step 1, the mixture is placed in a 40° C. water bath for reaction.
4. The method for preparing a supramolecular chiral helical nanocatalyst according to claim 1, characterized in that: In the step 2, the ratio of R / S-PAIPA nanofibers to ethanol is 5-8 mg: 3-5 mL.
5. The method for preparing a supramolecular chiral helical nanocatalyst according to claim 1, characterized in that: In the step 2, the R / S-PAIPA nanofibers obtained in the step 1 are transferred to ethanol for assembly, and the assembly is completed by standing at 25° C. for no less than 5 days.
6. The method for preparing a supramolecular chiral helical nanocatalyst according to claim 1, characterized in that: In the step three, the R / S-PAIPA spiral nanobelts are mixed with Fe3O4 respectively as follows: water is used as a solvent, Fe3O4 is dissolved in water, and then an aqueous solution containing R / S-PAIPA spiral nanobelts is added, the mass ratio of Fe3O4 and R / S-PAIPA spiral nanobelts is 0.5-2mg:15mg, and they are mixed at room temperature for 4h. After washing three times with ultrapure water and ethanol, the unloaded Fe3O4 is removed to obtain two supramolecular chiral nanocatalysts with excellent chiral selectivity.
7. A supramolecular chiral helical nanocatalyst prepared by the method according to any one of claims 1 to 6.
8. Use of the supramolecular chiral helical nanocatalyst according to claim 7 in enantioselective catalysis of R / S-DOPA.